Trial of Bhagat Singh - Noorani, A.G (New Delhi, 2012)
This book was written as a study in the politics of justice. Bhagat Singh's trial falls in the same gory tradition as Maharaja Nanda Kumar's in 1775 and Bahadur Shah Zafar's in 1858.
Keywords: India